Incidence of infectious complications following tube thoracostomy with and without use of antibiotic therapy: meta-analysis study - Fontelles,Mauro José (2001)
Objective - Thoracic lesions and resulting complications have gained increased importance in literature because they present a serious problem despite the generalized use of antibiotic therapy. Our study, therefore, aims at obtaining better estimates regarding the benefits obtained using antibiotic therapy in patients with isolated thoracic trauma and who have undergone closed chest drainage. Methods - Eight prospective and randomized studies were selected and meta-analysis was used to statistically associate the results. Results - The results demonstrated a statistical significance which favored the use of antibiotic therapy in preventing pleural empyema and a 9.25 (IC 95% 2.85 - 30.01) total relative risk for patients who did not receive antibiotic therapy. The total risk regarding all the infectious complications that occurred was 4.29 (IC 95% 2.70 - 8.97). Conclusion - The results of this meta-analysis study showed that antibiotic therapy effectively reduces the incidence of infectious complications in patients with isolated thoracic trauma, who have undergone closed pleural drainage.